2004
DOI: 10.1002/marc.200400173
|View full text |Cite
|
Sign up to set email alerts
|

Organically Modified Layered Titanate: A New Nanofiller to Improve the Performance of Biodegradable Polylactide

Abstract: Summary: The preparation and characterization of a new type of nanocomposite material that is based on biodegradable polylactide (PLA) and organically modified layered titanate, is reported. Layered titanate, modified with a N‐(cocoalkyl)‐N,N‐[bis(2‐hydroxyethyl)]‐N‐methylammonium cation, was used as a new nanofiller (OHTO) for the nanocomposite preparation. Wide‐angle X‐ray diffraction and transmission electron microscopy (TEM) analyses confirmed that titanate layers were intercalated and nicely distributed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(33 citation statements)
references
References 7 publications
0
33
0
Order By: Relevance
“…As fillers, an organo-layered titanate (HTO-ODA (0.2 equiv)-LL; Otsuka Chemical, Osaka, Japan) 11 and spherical titanate (Wako Chemical, Osaka, Japan) were used.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…As fillers, an organo-layered titanate (HTO-ODA (0.2 equiv)-LL; Otsuka Chemical, Osaka, Japan) 11 and spherical titanate (Wako Chemical, Osaka, Japan) were used.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…Okamoto and coworkers reported that the PLA nanocomposites with layered silicate or titanate enhanced the mechanical properties and increased the crystallization rate of PLA effectively. [28][29][30][31][32] PLA is one of a kind of polyesters. We focused on methods for improvement of properties of polyesters, especially most popular polyester of poly(ethylene terephthalate) (PET).…”
Section: Introductionmentioning
confidence: 99%
“…Addition of a nucleating agent to PLA is effective to improve the crystallization rate, and some nucleating agents, such as benzoic acid hydrazide, for PLA have been developed [6][7][8][9][10][11][12][13][14]. Nanocomposite of PLA is an effective method to improve the mechanical properties and increased the crystallization rate of PLA [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%